1995
DOI: 10.1037/0278-6133.14.7.622
|View full text |Cite
|
Sign up to set email alerts
|

Panel IV: Risk-taking and abusive behaviors among ethnic minorities.

Abstract: The health status and health outcomes of many ethnic minorities have remained poor, or have deteriorated, despite massive health promotion campaigns. Multiple factors that encourage ethnic minorities to engage in high-risk behaviors and those that discourage health promotive behaviors must be closely examined before any health interventions are likely to be successful in decreasing substance abuse, high-risk sex, accidental deaths and injuries, and violence. Cultural and contextual factors may put some ethnic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Blacks from the Caribbean constitute the largest subgroup of black immigrants in the US [29,30], with 1990 estimates suggesting that nearly 1 million persons were of English-speaking West Indian ancestry and 300,000 of Haitian ancestry [31]. To understand disparities and their origins, we must first define samples with greater specificity [32], beginning by studying specific subpopulations within the broad categorizations that are typically employed.…”
Section: Disparities In Screening and Repeat Screening: The Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…Blacks from the Caribbean constitute the largest subgroup of black immigrants in the US [29,30], with 1990 estimates suggesting that nearly 1 million persons were of English-speaking West Indian ancestry and 300,000 of Haitian ancestry [31]. To understand disparities and their origins, we must first define samples with greater specificity [32], beginning by studying specific subpopulations within the broad categorizations that are typically employed.…”
Section: Disparities In Screening and Repeat Screening: The Rationalementioning
confidence: 99%
“…Haitian women, in particular, showed a very high risk profile-high fatalism, high embarrassment and moderate worry-perhaps suggesting such variables may offer a particularly fruitful avenue for interventions in this group. More broadly, the pervasiveness of the differences in variables that have shown predictive value for screening behavior suggests that more clearly-defined samples are urgently needed [32].…”
Section: Ethnic Subpopulation Differences In Demographic Healthcare mentioning
confidence: 99%
“…23 Elevated rates of CFS in Latinos and African Americans compared with whites may be partly explained by a predominance of findings indicating consistently poor or deteriorating health status among certain underserved ethnic groups that face various forms of psychosocial stress. 48 Interacting factors contributing to poorer health status among underserved ethnic groups may include psychosocial stress, behavioral risk factors (use of alcohol and tobacco and lack of sufficient exercise), differences in health care practices (inadequate nutrition and lack of routine medical examinations), barriers to access to adequate health care (lack of health insurance and inadequate health care), and more hazardous occupations and environmental exposures. [49][50][51] In addition to these factors, Rogers and associates 52 highlight the importance of demographic variables as contributors to compromised health status.…”
Section: Commentmentioning
confidence: 99%
“…There are studies that have conflicting results on racially disparate driving behavior, including Lamberth's frequently cited 1996 Report to the American Civil Liberties Union, which found that Blacks did not differ from Whites in speeding behavior on Maryland highways (Ward, 2002) and Lange, Blackman, and Johnson's (2001) often-cited report of speeding on the New Jersey Turnpike, which found that Blacks are more likely to speed than Whites and at especially high rates of speed. The reason for the differences in findings may be the multiple and complex factors that seems to encourage high-risk behaviors (including red light running) in minorities that result in death and injury (Porter & England, 2000;Yee et al, 1995).…”
Section: Defining and Explaining Racial Profilingmentioning
confidence: 99%